Does the prolonged in vitro maturation of human oocytes influence the aneuploidy type? - Križančić Bombek, Lidija (Zdravniški vestnik, 2011)
Objective: In many stimulated infertility treatment cycles some oocytes are collected immature and can be matured in vitro (IVM). However, their safe clinical use is questionable because of their apparently low morphologic and genetic quality. We investigated the influence of the IVM duration on the type and frequency of chromosome abnormalities in germinal vesicle stage (GV) oocytes from stimulated cycles. Design: In vitro maturation of GV oocytes (from stimulated cycles) for 24 (Group - A) or 36 (Group - B) hours and subsequent fluorescent in situ hybridization analysis (FISH) of chromosomes 13, 16, 18, 21 and 22. Results: After maturation, chromosomes were undoubtedly analyzable in 102 oocyte-first polar body pairs. Aneuploidy rates in both groups did not differ statistically. However, within Group - B a significantly higher rate of hyperhaploidy over hypohaploidy was observed. Also, there was a significantly higher frequency of disomy than nullisomy in both groups, and the aneuploidy rate of chromosomes 18 and 22 was significantly increased in Group - B. Conclusion: The observed preferential excess over the loss genetic material and the increase in chromosome non-disjunction in the oocytes from Group - B, indicate a negative influence of prolonged IVM on chromosome segregation or conversely, suggests that GV oocytes which attain maturity later, possess more intrinsic abnormalities that result in aneuploidy.
Keywords: analiza; ginekologija; jajčne celice; kromosomi; oogeneza; reprodukcija